ANALISIS PENGARUH KEPERCAYAAN DAN NILAI JASA TERHADAP KEPUASAN PESERTA DIDIK PADA LEMBAGA PENDIDIKAN DAN KETERAMPILAN KHARISMA BANJARMASIN - Apriya Santi (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, The evaluation of trust and service value can build positive perception in an effort to give satisfaction to the customers. Trust and Service value in these cases are the parts of key factors in building long-term relationships and can be used as sources of competitive advantage for educational institutions and skills in maintaining and attracting learners. The purposes of this research were to determine and analyze the influences of trust and service value to satisfaction of students at the Educational Institutions and Skills Kharisma Banjarmasin. By using purposive sampling method, there are 34 samples of respondents from the entire population of students in LPK Kharisma. The analysis technique used is the Multiple Linear Regression. The results showed that there is not correlation between trust to satisfaction, but there is a positive and significant correlation between service value to the satisfaction of learners.